Analysis of the Obligation of Halal Certification for Food and Beverage Products among Non-Muslim Business Actors in Kaloran District - Mahdee Maduerawae; Imron Imron; Hidayatun Ulfa (Jurnal Syariah, Hukum, dan Ekonomi Islam, 2024)
This study examines the obligation of halal certification for food and beverage products produced by non-Muslim business actors in Kaloran District. The enactment of Law Number 33 of 2014 on Halal Product Assurance, as amended by Law Number 11 of 2020 on Job Creation, has transformed halal certification from a voluntary requirement into a mandatory legal obligation for all business actors, regardless of religious background. This policy aims to provide legal certainty and consumer protection, particularly for Muslim consumers who are religiously obliged to consume halal products. This research employs a qualitative approach with a normative-empirical method. Normative analysis is conducted through the examination of statutory regulations related to halal certification, while empirical data are obtained through field observations and interviews with non-Muslim food and beverage business actors in Kaloran District. The study reveals a significant gap between legal norms (das sollen) and their practical implementation (das sein). Most non-Muslim business actors have not yet obtained halal certification, and some are unaware of the mandatory nature of this obligation. Limited socialization, lack of administrative guidance, and perceptions of lengthy certification procedures are identified as the main obstacles to compliance. The findings indicate that the primary challenge in implementing mandatory halal certification does not lie in the legal framework itself but in its execution at the local level. Therefore, this study emphasizes the need for more effective socialization, institutional assistance, and simplified administrative procedures to ensure the effective enforcement of halal certification obligations. Strengthening these aspects is essential to achieving the objectives of consumer protection, legal certainty, and the development of Indonesia’s halal industry